Modeling and analysis of lignite particle drying based on the volume averaging method. Issue 1 (2nd January 2022) - Wan, Keji; Gao, Mingqiang; Xiao, Yawen; He, Qiongqiong; Miao, Zhenyong
Abstract: A mathematical model based on the volume averaging method and a corresponding numerical strategy were developed to investigate the drying behavior of lignite. Simultaneous and continuous measurements of weight and temperature profiles were carried out for a lignite particle by employing a self-designed tunnel dryer to verify the predictive model. It was shown that the simulated results were in good agreement with the measured values. Based on the model, the evolution and distribution of moisture, temperature, and water vapor pressure (WVP) in a lignite particle were studied. It is shown that the hysteresis effect of the evaporative surface caused a significant moisture gradient in particle, and from the surface to the center of the particle, WVP grew with a decreasing rate. A higher drying temperature could accelerate the evolution of moisture in the particle and promote the development of "increasing local moisture". The acceleration of the drying rate caused by increased temperature is less related to the moisture gradient but is greatly affected by the WVP. Furthermore, the humidity and temperature of the external environment of the lignite was also further studied based on above model. Thus, the model can be used for the optimization of the drying process parameters and can offer guidance for the development of new drying technologies.